Temperature dependent stacking fault energy of FeCrCoNiMn high entropy alloy. (November 2015) - Huang, Shuo; Li, Wei; Lu, Song; Tian, Fuyang; Shen, Jiang; Holmström, Erik; Vitos, Levente
Abstract: The stacking fault energy (SFE) of paramagnetic FeCrCoNiMn high entropy alloy is investigated as a function of temperature via ab initio calculations. We divide the SFE into three major contributions: chemical, magnetic and strain parts. Structural energies, local magnetic moments and elastic moduli are used to estimate the effect of temperature on each term. The present results explain the recently reported twinning observed below room-temperature and predict the occurrence of the hexagonal phase at cryogenic conditions.